PERANAN TEKNOLOGI INFORMASI DALAM PENYEDERHANAAN PROSES PENYAJIAN INFORMASI: STUDI KASUS PRODUKSI DAN PERSEDIAAN PT SSAM - Darudiato, Suparto (CommIT (Communication and Information Technology) Journal, 2007)
Article to analyse the selling information needs by paying attention to transaction simplicity process so itcan grow the custmer trust to the company. The research was done by a direct survey to the company by doingbusiness process survey, spreading questioner, and analyzing the needs of information. The research result wasproblems list and the user needs of information.Keywords: information technology, information dissemination, inventory, production